Current Advances in the Metabolomics Study on Lotus Seeds - Zhu, Mingzhi; Liu, Ting; Guo, Mingquan (Frontiers in Plant Science, 2016)
Lotus (Nelumbo nucifera), which is distributed widely throughout Asia, Australia and North America, is an aquatic perennial that has been cultivated for over 2,000 years. It is interesting to note that almost all parts of lotus are consumed food products, especially the seeds. Apart for the nutritive values of lotus, there has been increasing interest in its potential as a functional food due to it being a rich source of secondary metabolites, such as flavonoids and alkaloids. While this array of metabolites contribute to varied biological processes within the lotus seeds, they have also been reported to possess multiple health-promoting effects, including antioxidant, anti-amnesic, anti-inflammatory, and anti-tumor activities. Thus, the comprehensive profiling of these metabolites is of key importance to help understand their biological activities, and other chemical biology features. In this context, this review will provide an update on the current technological platforms, and workflows associated with metabolomic studies on lotus seeds, as well as insights into the application of metabolomics for the improvement of food safety and quality, assisted breeding, and promotion of the study of metabolism and pharmacokinetics of lotus seeds. It will also explore new perspectives and outline future challenges in this fast-growing research area.